Grant-flipping across Europe: How Portuguese artists navigate precarity to sustain aspirations beyond recognition - Borges, V. (Poetics, 2025)
This article examines how artists navigate precarious labour conditions through a practice we conceptualize as grant-flipping: the sequential pursuit of grants across national and institutional boundaries. We propose this concept as an analytical lens to understand how artists develop reactive strategies not only to sustain their careers, but also to pursue meaningful artistic aspirations amid growing dependence on institutional funding. While the literature on artistic labour often emphasizes reputational hierarchies and structural constraints, grant-flipping foregrounds the adaptive agency of artists and the core values that shape their professional trajectories. Drawing on Calouste Gulbenkian Foundation art grants, we carried out documental analysis of two databases, alongside 60 qualitative interviews and an online survey (N = 488) on grant-based funding. We present six paradigmatic artistic trajectories spanning different career stages and disciplines. Our findings portray how, rather than pursuing global recognition, artists seek relational embeddedness within transnational circuits, often moving through conservatories, residencies, and institutional collaborations. Grant infrastructures enable them to mitigate economic risks, navigate structural inequalities, and sustain long-term careers. By theorizing grant-flipping as a constrained strategy in response to national structural precarity, this article contributes to debates on artistic labour, cultural policy, and the uneven geographies of artistic production. It furthermore provides insights into how Portuguese artists exercise agency within increasingly global and institutionally mediated art fields.